Differential Effects of Classical vs. Sports Massage on Erector Spinae and Upper Trapezius Muscle Stiffness: A Shear-Wave Elastography Study in Young Women - Amadej Jelen; Erina Javornik; Manca Zupančič; Žiga Kozinc (MDPI AG, 2024)
Classical and sports massages are commonly used interventions, but their comparative effects on muscle stiffness remain unclear. Classical massage is more general and uses light to moderate pressure, and its main purpose is relaxation. Sports massage, on the other hand, is more specialized and targets the unique needs of massaged individuals using moderate to firm pressure. This study aimed to evaluate the impacts of classical and sports massages on the stiffness of the erector spinae (ES) and upper trapezius (UT) muscles. Fifteen recreationally active young women, aged 22.9 ± 1.2 years, underwent a randomized cross-over study (with three conditions). Participants received either a five-minute classical or sports massage or a passive rest as a control on distinct days. Muscle stiffness was assessed using shear-wave elastography. The ES shear modulus displayed a significant time effect (p < 0.001; η2 = 0.515) without noticeable differences between the conditions, and the time × massage-type interactions approached statistical significance (F = 2.014; p = 0.073). There was also a large and statistically significant effect of the time on the UT (F = 11.127; p < 0.001; η2 = 0.443). We could not prove that classical and sports massages reduced muscle stiffness. The absence of significant differences might be attributed to the specific intervention parameters (massage duration of 5 min) and the small, only young women sample size. Given some tendencies towards significant effects, larger sample sizes are needed to further investigate this research question.